Peningkatan Motivasi, Aktivitas, dan Kemampuan Berpikir Kritis Siswa Sekolah Dasar Melalui Quantum Teaching - Aka, Kukuh Andri (Jurnal Didaktika Pendidikan Dasar, 2025)
The problem of fourth grade students of state elementary school Besowo 2 year 2022/2023 on learning civics lesson, namely (1) the learning does not use an innovative model, so that students are less enthusiastic to respond to questions or instructions from teachers, and (2) students are less active in constructing knowledge, because learning is dominated by explanations and giving examples of questions from the textbook. Based on this, this study aims to improve motivation, activity, and critical thinking skills in Grade IV students of PPKn at state elementary school Besowo 2 in the 2022/2023 academic year. Design research is classroom action research (CAR). Research results showed improvement and success of teachers in making learning using Quantum Teaching, seen scores success in the first cycle reached 85.5% and 91% in the second cycle. Students’ motivation increased from 75 in the first cycle and 84 in the second cycle. Learning activities of students increased from 74 in the first cycle and 82.5 in the second cycle. Student critical thinking ability increased from 76 in the first cycle and 81 in the second cycle. During the learning using Quantum Teaching students’ motivation increased, activity increased student learning and after learning increases student critical thinking ability.